Toxicity of Methotrexate in RA: Case of Oral Ulcers and Pancytopenia - M, Deeksha; JK, Chethan Kumar; Dias, Akshay Louis; S, Mangala (Indian Journal of Pharmacy Practice)
Rheumatoid arthritis is a chronic autoimmune disease affecting approximately 1% of the population, primarily causing joint inflammation and leading to joint destruction, physical disability and cardiovascular disease. Methotrexate, a commonly used antimetabolite in rheumatoid arthritis treatment, is associated with toxicity, including mucositis and pancytopenia, particularly when used at high doses or without adequate folic acid supplementation. This report presents the case of a 69-year-old female with rheumatoid arthritis who developed bleeding oral ulcers, mucositis and difficulty swallowing while on methotrexate therapy. Laboratory investigations revealed pancytopenia, acute kidney injury on chronic kidney disease and atypical cells, resulting in a diagnosis of methotrexate-induced toxicity. The patient was treated with folinic acid, intravenous fluids and supportive care, including antibiotics for a lower respiratory tract infection and antifungal medication for oral candidiasis. Her condition improved, with healing of the ulcers and normalization of her blood cell counts. This case underscores the importance of regular monitoring of blood counts, renal function and methotrexate serum levels to prevent methotrexate toxicity. Clinicians should remain vigilant for methotrexate-related complications, especially in elderly patients with renal impairment and irregular follow-up care. Early detection and prompt treatment are essential to prevent life-threatening consequences.
Keywords: Dihydrofolate Reductase; Dihydrofolate; Methotrexate; Mucositis; Rheumatoid Arthritis; Tetrahydrofolate+